Psychometric Properties of the Smartphone Distraction Scale in Chinese College Students: Validity, Reliability and Influencing Factors - Zhao, Xueyang; Hu, Ting; Qiao, Guiyuan; Li, Chaoyang; Wu, Man; Yang, Fen; Zhou, Jing (Frontiers in Psychiatry, 2022)
Aim: The objective of this study was to evaluate the Chinese version of the Smartphone Distraction Scale (C-SDS), which is an easy-to-use tool for screening the risk of smartphone distraction in Chinese college students. Methods: The C-SDS, the Smartphone Addiction Scale - Short Version (SAS-SV), the Fear of Missing Out scale (FoMO) and the Metacognition about Smartphone Use Questionnaire (MSUQ) were used in a sample of 1,002 Chinese college students to test smartphone distraction and its influencing factors. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were performed to test measurement properties and factor structures of the C-SDS. Multi-variable linear regressions examined the relationships of sex, age, education level, the purpose of using a smartphone, usage of smartphone (hours per day), fear of missing out, smartphone addiction and positive and negative metacognitions about smartphone use with the C-SDS. Results: EFA showed a 3-factor structure, which consisted of attention impulsiveness, multitasking and emotion regulation. CFA showed that the 3-factor demonstrated an overall better model fit (RMSEA = 0.07, SRMR = 0.05, CFI = 0.94, TLI = 0.93). The C-SDS showed internal consistency (Cronbach’s α = 0.88, McDonald’s Omega ω=0.88). Findings included that negative metacognition about smartphone use was most correlated with the C-SDS (b= 0.73; p<0.001). Smartphone addiction, positive metacognition about smartphone use and fear of missing out also correlated with the C-SDS (b= 0.66, p<0.001; b= 0.53, p<0.001; b=0.40, p<0.001, respectively). The study shows that males compared to females (b= -1.65; p=0.003), was had a higher C-SDS score. Conclusion: The C-SDS was valid and reliable for assessing the distraction of using smartphones in the Chinese context. Females, the purpose of using a smartphone, smartphone usage (hours per day), fear of missing out, smartphone addiction and positive and negative metacognitions about smartphone use were related to the C-SDS.